Rapid Chemical Reaction Monitoring by Digital Microfluidics‐NMR: Proof of Principle Towards an Automated Synthetic Discovery Platform. Issue 43 (12th September 2019) - Wu, Bing; von der Ecken, Sebastian; Swyer, Ian; Li, Chunliang; Jenne, Amy; Vincent, Franck; Schmidig, Daniel; Kuehn, Till; Beck, Armin; Busse, Falko; Stronks, Henry; Soong, Ronald; et al.
Abstract: Microcoil nuclear magnetic resonance (NMR) has been interfaced with digital microfluidics (DMF) and is applied to monitor organic reactions in organic solvents as a proof of concept. DMF permits droplets to be moved and mixed inside the NMR spectrometer to initiate reactions while using sub‐microliter volumes of reagent, opening up the potential to follow the reactions of scarce or expensive reagents. By setting up the spectrometer shims on a reagent droplet, data acquisition can be started immediately upon droplet mixing and is only limited by the rate at which NMR data can be collected, allowing the monitoring of fast reactions. Here we report a cyclohexene carbonate hydrolysis in dimethylformamide and a Knoevenagel condensation in methanol/water. This is to our knowledge the first time rapid organic reactions in organic solvents have been monitored by high field DMF‐NMR. The study represents a key first step towards larger DMF‐NMR arrays that could in future serve as discovery platforms, where computer controlled DMF automates mixing/titration of chemical libraries and NMR is used to study the structures formed and kinetics in real time. Abstract : Automated discovery : A combination of microcoil nuclear magnetic resonance (NMR) and digital microfluidics (DMF) allows sub‐microliter volumes of reagents to be moved and mixed inside the NMR spectrometer to initiate reactions. This permits monitoring reactions of scarce or expensive reagents and opens up the potential for future automated synthetic discovery platforms.